Development of E-MORPITT (Electronic Module of the 1975 East Timor Integration Struggle-Reconciliation) for History Learning - Kusuma, Yolan Sadewa; Jauhari, Najib; Subekti, Arif (Universitas Negeri Semarang, 2024)
This article aims to describe the development of the E-Module for the 1975-Reconciliation struggle for East Timor Integration. Indonesian history teaching materials that discuss the struggle for 1975-East Timor Integration-Reconciliation are still lacking, even the topic of reconciliation has not been discussed in the curriculum. The next problem is the absence of teaching materials that can be accessed as a reference in schools that discuss the topic of reconciliation. The problems of this research are, how is the development of the E-Module teaching materials, whether the E-Module is appropriate as a teaching material, whether the E-Module is effective as a teaching material. This study uses research and development methods. The research steps are looking for potentials and problems in the curriculum, collecting data on sources of teaching materials, designing, validating, revisions that are given criticism and expert advice, small group trials, revising if they find deficiencies, conducting final large group trials, revision before production, and producing teaching materials that have been tested. The results of the E-Modul research have met the objectives of the development, namely valid, practical and effective. Materials and media experts gave a very valid value. Practitioners (teachers), small group trials, and large groups all rated the E-Module as practical and feasible to use. From the effectiveness test, the E-Modul provides effective results in improving student learning outcomes through pretest and posttest evaluations.